PENGARUH KUALITAS PELAYANAN, HARGA DAN PROMOSI TERHADAP LOYALITAS PELANGGAN MELALUI KEPUASAN PELANGGAN PT. MATAHARI SILVERINDO JAYA SEMARANG - Padma Triscahyaning Wibawa; Naili Farida; Sari Listyorini (Jurnal Ilmu Administrasi Bisnis, 2014)
Matahari Silverindo Jaya is a company who have to proceed glass and mirror. This company was build in 2001 in Candi Industrial Area Semarang, Central Java, Indonesia. To improve their profit, this company make a new product, such as tempered glass and porselein. After that, Matahari Silverindo Jaya make their product with machine.The purpose of this research is to determine the influence of service quality, price and promotion on loyalty through cotumer satisfaction at Matahari Silverindo Jaya Company Semarang. The type of this research is Explanatory Research with data used in this study is primary data obtained using  questionnaire and library research. Analysis of data using simple linear regression and multiple regression test with SPSS 16.0. While hypothesis testing using the t test, f test, correlation coefficient, and the coefficient of determination.Based on the analysis it can be concluded that there is a positive and significant influence between service quality to satisfaction, positive and significant influence between price to satisfaction, positive and significant influence between promotion to satisfaction, posiitive and significant influence between service quality, price and promotion to satisfaction between service quality to loyalty, positive and significat influence between price to loyalty, positive and significant influence between promotion to loyalty, there is positive and significant influence between quality of the service, price and promotion to loyalty, there is positive and significant influence between service quality to loyalty.Sugestion for the company is to meke their product on time and with the good quality of the basic ingredients. Besides that, the company must improve their delivery and promotion, in order for their product information can be accept by the consumer.